Uganda’s Public Health Emergency Supply Chain System in the Awake of COVID-19 Emergency Response: Method and Performance - Wasswa, John Hans; Olowo Oteba, Martin; Katumba, Ahmed (International Journal of Science and Research (IJSR), 2020)
Global Health Supply Chain Systems have been unprecedentedly strained to the limits following the coronavirus disease 2019 (COVID-19) pandemic outbreak, raising a concern of the possible magnitude of impact likely to be posed on health supply chain systems of low-income countries like Uganda. Uganda experienced its first COVID-19 outbreak on 21st March 2020, 10 days shortly after World Health Organization’s (WHO) pandemic declaration. Ever since then, the number of cases in Uganda has gone on to rise every day. This paper aims to examine in detail the experiences and effectiveness of Uganda’s health supply chain system in preparedness and response to COVID-19 outbreak. All components of Uganda’s public health emergency (PHE) supply chain system and activities undertaken were examined. Ministry of Health (MoH) reports, Logistic Subcommittee (LSC) reports and published journals on COVID-19 were used to inform this paper. Upon declaration of the novel coronavirus (SARS-CoV-2) outbreak a Public Health Emergency of International Concern by WHO on 30th January 2020, MoH activated the Public Health Emergency Operations Center, National Task Force and District Task Forces to coordinate the COVID-19 preparedness and response. On 31st January 2020 the LSC activated the PHE supply chain system components and activities. The National Medical Countermeasures plan was activated. Quantification, forecasting and pipeline monitoring for possible logistics needs of COVID-19 was conducted for 136 districts, 8 regional prepositioning centers, 17Regional referral hospitals, over 80 public hospitals, 89 quarantine centers, and 75points of entry. The electronic Emergency Logistics Management Information system (eELMIS) was activated to coordinate all emergency supply chain information and regular reporting of stock status at all levels. Eight (8) regional prepositioning centers for stockpiling COVID-19 supplies were activated. In conclusion, the COVID-19 epidemic outbreak provided a stun on-field test for Uganda’s young PHE supply chain system giving it an opportunity to close all the gaps not earlier well-known, and consequently making it even stronger for future epidemics. This paper therefore shares Uganda’s experiences, methods and performance and future lessons from which other countries’ health supply chain systems can learn from.
Keywords: Public health emergency; Health supply chain system; Medical countermeasures; COVID-19 preparedness and response; SARS-CoV-2; Global Health Security; Uganda